Experimental and numerical investigations of S700 high strength steel tubular section stub columns after exposure to elevated temperatures - Zhong, Yukai (2022)
This paper reports comprehensive experimental and numerical investigations into the cross-sectional behaviour and residual resistances of S700 high strength steel square and rectangular hollow section stub columns after exposure to elevated temperatures. The experimental investigation employed three cold-formed S700 high strength steel square and rectangular hollow sections, and for each cross-section, five geometrically identical stub column specimens were prepared and tested after exposure to different levels of elevated temperature, namely 30 °C, 400 °C, 600 °C, 800 °C and 1000 °C. This was followed by a numerical investigation, where finite element models were initially developed and validated against the experimental results and then adopted to conduct parametric studies to generate further numerical data over a wide range of cross-section dimensions. Owing to the absence of design standards for high strength steel structures after exposure to elevated temperatures, the corresponding ambient temperature design rules, as provided in the European code, American specification and Australian standard, were evaluated for their applicability to S700 high strength steel square and rectangular hollow section stub columns after exposure to elevated temperatures. The evaluation results indicated that the ambient temperature slenderness limits for internal plate elements in compression, as specified in the three considered design standards, are accurate and safe when used for cross-section classification of S700 high strength steel square and rectangular hollow section stub columns after exposure to elevated temperatures. In terms of the cross-section compression resistance predictions, the Australian standard was shown to provide accurate, consistent and safe predicted resistances for S700 high strength steel square and rectangular hollow section stub columns after exposure to different levels of elevated temperature. The European code and American specification were found to yield accurate, consistent and safe post-fire compression resistance predictions for S700 high strength steel non-slender square and rectangular hollow section stub columns but over-predict the post-fire compression resistances for those slender section stub columns, owing principally to the employment of unsafe effective width expressions.